2013
DOI: 10.1111/dme.12256
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal temporal patterns of hypoglycaemia in hospitalized people with diabetes may reveal potentially correctable factors

Abstract: Hypoglycaemia occurs more frequently between 21.00 and 09.00 h in hospitalized patients receiving treatments that can cause hypoglycaemia. This may be related to insufficient carbohydrate intake during this period, and is potentially preventable by changes in catering practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The current study was designed to determine whether similar or other temporal patterns of hypoglycaemia exist in other NHS hospitals and, if so, to consider the possible reasons for any observed differences and potential preventative strategies. Additionally, in the previous study, there appeared to be more hypoglycaemic readings in those on sulfonylurea therapy than anticipated, but that study was not specifically designed to examine this 11. As a result of this anecdotal observation and in view of the ADA's abandonment of sulfonylurea therapy in the inpatient setting, the current study was also designed to compare hypoglycaemic rates and patterns in sulfonylurea and insulin-treated inpatients.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The current study was designed to determine whether similar or other temporal patterns of hypoglycaemia exist in other NHS hospitals and, if so, to consider the possible reasons for any observed differences and potential preventative strategies. Additionally, in the previous study, there appeared to be more hypoglycaemic readings in those on sulfonylurea therapy than anticipated, but that study was not specifically designed to examine this 11. As a result of this anecdotal observation and in view of the ADA's abandonment of sulfonylurea therapy in the inpatient setting, the current study was also designed to compare hypoglycaemic rates and patterns in sulfonylurea and insulin-treated inpatients.…”
Section: Introductionmentioning
confidence: 91%
“…In a recent study of inpatient hypoglycaemia in one NHS hospital, we found that more than two-thirds of all hypoglycaemic readings occurred between 21:00 and 8:59 11. The current study was designed to determine whether similar or other temporal patterns of hypoglycaemia exist in other NHS hospitals and, if so, to consider the possible reasons for any observed differences and potential preventative strategies.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4] In the UK National Diabetes Inpatient Audit, hypoglycaemia occurred in 23.4% of inpatients with diabetes and 2.2% of these patients required parenteral glucose or glucagon. 5 The frequency and severity of hypoglycaemia has been associated with an increase in pre-and post-discharge mortality and length of admission.…”
Section: Introductionmentioning
confidence: 99%
“…The group has already published their work in parts in international journals to share best practice. 12,13 The judges particularly liked the fact that the innovation was comprehensive, multicentred, impactful and was shared well nationally through presentations and publications in reputed journals.…”
Section: Resultsmentioning
confidence: 99%